BIOCHEMICAL ANALYSIS OF THE SPECIES OF NOSTOC COMMUNE - Abdurahmon Sheraliev (Research Focus International Scientific Journal, 2025)
This article describes the morphology of the representative of cyanoprokaryotes - Nostoc commune, its distribution, nutritional elements - protein, lipid, carbohydrate, vitamin, pigment and microelements. The data obtained by many researchers on the amounts of these bioactive substances were compared and analyzed. Also, Nostoc commune is a universal and promising object of biotechnology, has high growth rates, and the cultivation process does not require large investments. In addition, it is a source of biologically active compounds that can be used in food, medicine and agriculture.